Evaluasi Sistem Informasi Pendaftaran Rumah Sakit Di Rumah Sakit Nasional Diponegoro Dengan Menggunakan Metode COBIT 5 Domain MEA - sherlina, maria dominika mazzarella; Chotimah, Siti Noor (Universitas Multi Data Palembang, 2024)
The use of technology is currently very necessary, in particular the use of the Hospital Information Management System (HIMS). Proper implementation of HIMS will produce accurate, integrated information. HIMS can be implemented within the framework of the COBIT 5 (Control, Evaluation and Assessment) MEA domain. The research carried out is quantitative. The source of data for this study is primary, via questionnaires. The objective of this study was to evaluate the hospital registration information system at Diponegoro National Hospital. The study population consisted of IT staff and medical records unit staff, particularly registration staff. The analysis was carried out using the MEA's capability level assessment process for each domain. The results showed that Diponegoro National Hospital's hospital registration information system achieved a capability level of 2,75 or at level 3 (established process). The MEA01 domain measurement has a capability of 3.81 or at level 4, the MEA02 domain has a capability level of 0.31 or at level 0, and the MEA03 domain has a capability level of 4.12 or at level 4. There are a number of influencing factors, such as the control system not having been optimally implemented, and the lack of human resources affecting the operation of the systems.